Multistage and coordinated planning of the expansion of transmission systems - Escobar, A. H.; Gallego, R. A.; Romero, R. (Institute of Electrical and Electronics Engineers (IEEE), 2004)
In this paper, an efficient genetic algorithm (GA) is presented to solve the problem of multistage and coordinated transmission expansion planning. This is a mixed integer nonlinear programming problem, difficult for systems of medium and large size and high complexity. The GA presented has a set of specialized genetic operators and an efficient form of generation of the initial population that finds high quality suboptimal topologies for large size and high complexity systems. In these systems, multistage and coordinated planning present a lower investment than static planning. Tests results are shown in one medium complexity system and one large size high complexity system.
Keywords: multistage planning; optimization; network expansion planning; genetic algorithms